Changes in precipitation extremes over the Kelantan River Basin, Malaysia. (15th December 2016) - Tan, Mou Leong; Ibrahim, Ab Latif; Cracknell, Arthur P.; Yusop, Zulkifli
ABSTRACT: Regional spatio‐temporal assessment of extreme precipitation is essential to develop better climate adaptation and mitigation strategies. This study evaluated trends in precipitation extremes from 1985 to 2014 in the Kelantan River Basin (KRB), Malaysia. Forty‐one climate stations that had <10% missing data, and which passed the data quality control and homogeneity tests were selected. Trends of 14 precipitation extreme indices recommended by the Expert Team on Climate Change Detection and Indices that related to duration, threshold, absolute, relative and percentile indices were analysed using the Mann–Kendall and Sen's tests. Generally, most of the regional precipitation extremes' indices had increased trends, except the consecutive dry days and consecutive wet days, which are quite consistent with global scale trends studies. On a monthly scale, the maximum 5‐day precipitation amount (Rx5d) had increasing trends in January (34.91 mm decade −1 ) and December (13.96 mm decade −1 ), by field significance at 95% confidence level. For spatial context, most of the stations with significant trends were distributed in the south‐western (mountainous) and northern (near‐coastal) regions. In the Tropics, the KRB's extremes indices trends had a similar pattern to the West Pacific, Indian Ocean and Caribbean regions, but were different from Western Thailand, the South China Sea and the North Inter‐tropical Convergence Zone, showing that trends of precipitation extreme events are different regionally. Overall, the Pacific Decadal Oscillation, Multivariate El‐Niño Southern Oscillation Index, Indian Ocean Dipole and Madden‐Julian Oscillation had a significant relationship with all precipitation extremes' indices, and they are contributors to climate changes in this basin.